Value of graduated compression stockings in deep venous insufficiency. Issue 6217 (22nd March 1980) - Horner, J; Fernandes, J; Fernandes, E; Nicolaides, A N
Abstract : The effect on elastic stockings on ambulatory venous pressure was investigated in 22 limbs with deep venous insufficiency. The failure of some elastic stockings to reduce the ambulatory venous pressure in some limbs is due to the lack of graduated compression, which is caused by ankle-calf disproportion--narrow ankles and wide calves. This can be recognised by using the pressure-girth profile and corrected by specially made stockings with increased tension at the ankle. A pressure-girth profile established for each stocking enabled the exact compression exerted by the stocking along the length of each limb to be determined. Elastic stockings exerting a graduated compression between ankle and calf induced a reduction in the ambulatory venous pressure in all but one limb. The greater the degree of graduated compression between ankle and calf exerted by the stocking, the greater the fall in ambulatory venous pressure. This may explain the beneficial effect of compression in limbs with venous ulceration.